THE INFLUENCE OF SELF-DISCLOSURE ON PRISONER RESILIENCE AT CLASS IIB STATE DETENTION CENTER PRABUMULIH - Kuncoro, M Satrio Gadang; Wibowo, Padmono (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study focuses on the influence of self-disclosure on the resilience of drug offenders in Class IIB Prabumulih Prison. Self-disclosure, defined as the process of sharing personal information and feelings with others, plays a crucial role in helping inmates adapt to the challenging prison environment. By openly communicating their thoughts and experiences, inmates can foster supportive relationships with peers and prison staff, which can significantly impact their resilience. Resilience, in this context, refers to the ability of individuals to endure and recover from stressors and difficult situations, such as the experience of incarceration. It encompasses various dimensions, including emotional strength, adaptability, and social support. This research employs a quantitative methodology, utilizing questionnaires to collect data from inmates regarding their levels of self-disclosure and resilience. The findings reveal a positive relationship between these two variables, suggesting that higher levels of self-disclosure are associated with greater resilience among inmates. This research contributes to the understanding of psychological dynamics within correctional facilities and underscores the importance of fostering communication among inmates as a means to enhance their resilience. Keywords: Self-Disclosure; Resilience; Drug Offenders; Class IIB Prabumulih Prison